Genome-wide RNAi screening identifies human proteins with a regulatory function in the early secretory pathway - Simpson, Jeremy; Joggerst, Brigitte; Laketa, Vibor; Erfle, Holger; Bechtel, Stephanie; Wiemann, Stefan; Ellenberg, Jan; Pepperkok, Rainer (Nature cell biology, 2012)
The secretory pathway in mammalian cells has evolved to facilitate the transfer of cargo molecules to internal and cell surface membranes. Use of automated microscopy-based genome-wide RNA interference screens in cultured human cells allowed us to identify 554 proteins influencing secretion. Cloning, fluorescent-tagging and subcellular localization analysis of 179 of these proteins revealed that more than two-thirds localize to either the cytoplasm or membranes of the secretory and endocytic pathways. The depletion of 143 of them resulted in perturbations in the organization of the COPII and/or COPI vesicular coat complexes of the early secretory pathway, or the morphology of the Golgi complex. Network analyses revealed a so far unappreciated link between early secretory pathway function, small GTP-binding protein regulation, actin cytoskeleton organization and EGF-receptor-mediated signalling. This work provides an important resource for an integrative understanding of global cellular organization and regulation of the secretory pathway in mammalian cells.